PENINGKATAN HASIL BELAJAR IPAS MATERI EKOSISTEM MELALUI MEDIA DIGITAL INTERAKTIF DAN VIDEO PEMBELAJARAN DI SD - Alfia Nailis Sa’adah; Faiza Alvi Millati; Firyal Naufali Muttaqin; Irma Arifah; Honest Ummi Kaltsum (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to improve IPAS learning outcomes through the use of interactive digital media and learning videos. The type of research used is Classroom Action Research (PTK) with the Kemmis and McTaggart model, which consists of four stages in each cycle: planning, action implementation, observation, and reflection. The research was conducted in three cycles, with lesson plans developed jointly by teachers and researchers in each cycle. This research was conducted at SD Muhammadiyah 8 Jagalan Surakarta City for students in class III B, with ecosystem material in the odd semester of the 2024/2025 school year. The population involved in this study were 23 students. Data collection techniques include tests (formative evaluation) and non-tests in the form of observation, interviews, and documentation. The results showed an increase in the average score of learning outcomes, from 58.69 in the pre-cycle to 66.08 in cycle I, and increased again to 83.69 in cycle II. Because 87% of students achieved a score of more than or equal to 75 (KKTP), this research was declared successful.